Semi-Direct Democracy and the Possibility of Implementing its Manifestations in the Kurdistan Region/Iraq - Rahman, Shalaw Sabah Abdul (Journal of Legal and Political Studies, 2014)
Semi-direct democracy included several ways to the people's participation in the exercise of power in the state along its representatives in parliaments, and that the application of this system in the region required several repercussions of the most prominent of the inadequacy of the election process for the participation of the people to exercise their right of political By this, it is the other side that the lack of effective control over the work of people's deputies led to a decline in the role of parliament in achieving the wishes and interests of the people, that the manifestations of semi-direct democracy enables voters to impose effective control over the House of Representatives and their actions, as well as the issuance of this legislation are consistent with the views of the people and the same tendencies
Keywords: Semidirect democracy; parliaments; House of Representatives; Legislation